Matricaria recutita extract associated with norfloxacin or cephalexin enhances the antimicrobial activity of these drugs against Staphylococcus aureus - Rodrigo Rafael Maia (Biotemas, 2017)
Emergence of bacterial infections, including those associated with Staphylococcus aureus, brings up a need for searching new and more effective strategies for clinical treatment. The use of medicinal plants associated with conventional antibiotics may represent a therapeutic option. Currently, studies evidence the synergistic effect achieved by combining plant extracts with antibiotics. Our objective was evaluate the in vitro antimicrobial activity and bactericidal kinetics of Matricaria recutita extract (chamomile) and its association with cephalexin and norfloxacin on clinical isolates of S. aureus from bovine origin, characterized as resistant. The tests were performed by method of dilution in solid medium to determine the Minimum Inhibitory Concentration (MIC). In both combinations of M. recutita extract with antibiotics norfloxacin and cephalexin, we observed MIC in dilution 1:64, corresponding to 8μg/mL of the antibiotic and 13.43 μg/mL of extract. Cephalexin associated with chamomile extract produced a effect of the combination in 75% of samples in their MIC. The combination of natural products frequently used by the population with the antibiotics tested in this study, could represent a therapeutic option for treatment of infections caused by S. aureus, as well as the prevention of the increasing development of resistance.